Long-range planning : the executive viewpoint - Warren, E Kirby (Prentice Hall Englewood Cliffs, NJUS, 1966)
Highlights importance of long-range planning to national economy. Shows how corporate planning should not be done and discusses the nature of problems only business leaders can solve. Indicates major obstacles to successful planning. Shows how the absence of effective means of measuring and evaluating long-range planning leads to undesirable responses at operating levels. Outlines the components of a good measurement and control system for the evaluation of long-range planning efforts.